The impact of providing feedback to students as future professionals on their professional calling - Saveljeva, Regina; Rupšienė, Liudmila (Social Welfare: Interdisciplinary Approach, 2016)
Researchers express ideas about the relationship between feedback provided during the studies and students’ professional calling and raise hypotheses about the impact of certain elements of feedback on some aspects of professional calling, however, empirical evidence of the impact of feedback on students’ professional calling is still lacking. The article raises the problematic question: "What is the impact of providing feedback to students as future professionals on their professional calling?" The accomplished quasi-experiment and post-experimental testing of 110 students of the social pedagogy study programme has revealed that providing feedback to students as future professionals during their studies has an impact on their professional calling.